Unhygienic stool-disposal practices among mothers of children under five in Cambodia: Evidence from a demographic and health survey. - Pisey Vong; Pannee Banchonhattakit; Samphors Sim; Chamroen Pall; Rebecca S Dewey (PLoS ONE, 2021)
Background Unhygienic disposal of children's stools affects children's health in terms of their susceptibility to many diseases. However, there are no existing studies into the impact of unhygienic stool disposal in Cambodia. Therefore, this study aimed to identify factors associated with the unhygienic disposal of children's stools among children under the age of five in Cambodia. Methods An analytical cross-sectional study was conducted using data from the Cambodia Demographic and Health Survey (CDHS) 2014. A multivariable binary logistic regression was conducted using Stata to analyze factors associated with the unhygienic disposal of children's stools. Results Overall, the prevalence of practicing unhygienic disposal of children's stools was 29.27% (95%CI: 27.51%- 31.09%). Factors statistically associated with this practice were: living in the Central Plain, Plateau and Mountains, Coastal and Sea regions (AOR = 1.65; 95% CI: 1.33-2.04), (AOR = 2.53; 95% CI: 1.98-3.24) and (AOR = 4.16; 95% CI: 3.15-5.48) respectively, poor household wealth (AOR = 1.58; 95% CI: 1.31-1.91), the mother having no education (AOR = 1.45; 95% CI: 1.14-1.85), a high number of children aged under five (AOR = 1.11; 95% CI: 1.03-1.20), being in the "other" religious category (AOR = 1.77; 95% CI: 1.25-2.51), living in a household with unimproved toilet facilities (AOR = 1.22; 95% CI: 1.11-1.34), living in a household with inadequate hygiene (AOR = 1.33; 95% CI: 1.12-1.59), and the household not being visited by a family planning worker in the last year (AOR = 1.45; 95% CI: 1.19-1.77). However, an increase in the child's age by even a month had significant negative associations with unhygienic practice (AOR = 0.65; 95% CI: 0.60-0.70), even when controlling for other covariates. Conclusion Almost one third of the mothers do not practice hygienic disposal of children's stools in Cambodia. Unhygienic practices were more prevalent in certain regions, and were also associated with low wealth, lack of education, an increase in the number of children under five in the household, religion, lack of sanitation and access to healthcare professionals. Conversely, the child's age was found to be positively associated with the hygienic disposal of children's stools.